The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s1047-8477(03)00036-4
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crystal growth as revealed by atomic force microscopy

Abstract: Direct visualization of macromolecular crystal growth using atomic force microscopy (AFM) has provided a powerful tool in the delineation of mechanisms and the kinetics of the growth process. It has further allowed us to evaluate the wide variety of impurities that are incorporated into crystals of proteins, nucleic acids, and viruses. We can, using AFM, image the defects and imperfections that afflict these crystals, the impurity layers that poison their surfaces, and the consequences of various factors on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 52 publications
(64 reference statements)
1
41
1
Order By: Relevance
“…The characteristic interstep distance in these macrosteps [30-60 nm (39)] is significantly smaller than the mean cluster diameter (250 ± 50 nm). Incorporation of a solid amorphous cluster or a microcrystal on a sloped surface would not lead to a perfect merging of both phases (40), which contradicts numerous observations made in this work; (ii) on many occasions, we detected microcrystals that sedimented on a single macrocrystal (Fig. 3C) and time-lapse imaging showed that these microcrystals are not a source of large multilayer stacks, hence no successful fusion was made with both lattices.…”
Section: Resultscontrasting
confidence: 84%
“…The characteristic interstep distance in these macrosteps [30-60 nm (39)] is significantly smaller than the mean cluster diameter (250 ± 50 nm). Incorporation of a solid amorphous cluster or a microcrystal on a sloped surface would not lead to a perfect merging of both phases (40), which contradicts numerous observations made in this work; (ii) on many occasions, we detected microcrystals that sedimented on a single macrocrystal (Fig. 3C) and time-lapse imaging showed that these microcrystals are not a source of large multilayer stacks, hence no successful fusion was made with both lattices.…”
Section: Resultscontrasting
confidence: 84%
“…[Tangential growth as a whole was examined by Burton, Cabrera, and Frank (12); Frank's contribution was the analysis of screw dislocations (14)]. These 2 processes produce characteristic target and spiral patterns seen at the molecular scale in solid crystals (15). These same patterns are visible in the conspicuous features of the surface of nacre at the mesoscale in Fig.…”
Section: Liquid-crystal Layer Growth Model Of Nacrementioning
confidence: 96%
“…[11][12][13][14] In situ AFM studies of differing resolution have been reported for a number of MOFs, [15][16][17][18][19] revealing valuable information concerning their crystal growth and the growth of nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%